The Importance of Religious Education in the Digital Era - Muaddyl Akhyar; Nurfarida Deliani; Khadijah Khadijah (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
Digital religious education has emerged as a solution to strengthen individual character in the digital era, considering the rapid technological advancements and the high engagement of the younger generation in the online world. This study aims to analyze the role of digital religious education in shaping positive character, as well as the challenges related to the spread of negative content on digital platforms. Through a literature review, this research examines sources related to the influence of social media and technology in disseminating religious values, character strengthening, and the importance of digital literacy. The findings indicate that digital religious education has great potential to strengthen character through flexibility, interactivity, and the delivery of religious teachings relevant to contemporary challenges. However, challenges related to content quality and the spread of negative content remain major obstacles that need to be addressed through supervision and improved digital literacy. This study suggests the importance of collaboration between technology, religious education, and regulation in creating a digital environment that supports holistic character development.